Genericity and Markovian Behavior in Stochastic Games - Haller, Hans; Lagunoff, Roger (Econometrica, 2000)
This paper examines Markov perfect equilibria of general, finite state stochastic games. Our main result is that the number of such equilibria is finite for a set of stochastic game payoffs with full Lebesgue measure. We further discuss extensions to lower dimensional stochastic games like the alternating move game.